"But What About Feminist Porn?": Examining the Work of Tristan Taormino. (11th April 2016) - Whisnant, Rebecca
This article examines the work of Tristan Taormino, a prominent self-described feminist pornographer, in order to illustrate themes and commitments common among those who produce, perform in, and/or support feminist pornography. I argue that her work is burdened by thin and limited conceptions of feminism, authenticity, and sexual ethics, as well as by the profit-based exigencies of producing "feminist porn" within the mainstream pornography industry. I conclude that, if indeed feminist pornography is possible, Taormino's work falls far short of the mark. Public Health Significance Statement: This study suggests that Taormino's pornographic films are unlikely to have salutary effects on the sexual and relational lives of their consumers.